Utilization of Digital Marketing and Financial Report Recording Training as an Effort to Increase Umkm Income in Bitungsari Village, Kec. Ciawi Kab. Bogor - Widi Lusiana; Nindya Eka Putri; Jihana Salma Zahra; Debi Oktaviani; M Rizky Purnama; One Seapfry; Siti Nur Aulia; Lilis Alsucia; Isabela Cikitha; Saepul Rahman; Maria Magdalena Melani (PT FORMOSA CENDEKIA GLOBAL, 2022)
UMKM Keripik Pisang Kepok 2R and Bu Nana Cake & Pempek are one of the individual businesses in the field of snacks located in the Bitungsari Village area, Ciawi District, Bogor Regency. In each marketing process, the two UMKM already have an appropriate target market. However, the two UMKM still do not understand about financial reports and product marketing which are only in the surrounding area, so that with the Pengabdian Masyarakat program they can provide training assistance on simple financial reports, marketing and promotion through Digital Marketing.